Enhancement of Light Extraction Efficiency Using Wavy-Patterned PDMS Substrates - Jian Cheng Bi; Kyo-Cheol Kang; Jun-Young Park; Junbeom Song; Ji-Sung Lee; Hyejung Lim; Young Wook Park; Byeong-Kwon Ju (Nanomaterials)
This study introduces an organic light-emitting diode (OLED) light extraction method using a wavy-patterned polydimethylsiloxane (PDMS) substrate created via oxygen (O2) plasma treatment. A rapid fabrication process adjusted the flow, pressure, duration, and power of the O2 plasma treatment to replicate the desired wavy structure. This method allowed the treated samples to maintain over 90% total transmittance and enabled controlled haze adjustments from 10% to 70%. Finite-difference time-domain (FDTD) simulations were employed to determine optimal amplitudes and periods for the wavy structure to maximize optical performance. Further experiments demonstrated that bottom-emitting green fluorescent OLEDs constructed on these substrates achieved an external quantum efficiency (EQE) of 3.5%, representing a 97% improvement compared to planar PDMS OLEDs. Additionally, color purity variation was minimized to 0.044, and the peak wavelength shift was limited to 10 nm, ensuring consistent color purity and intensity even at wide viewing angles. This study demonstrates the potential of this cost-effective and efficient method in advancing high-quality display.